2014 IST-Africa Conference Proceedings 2014
DOI: 10.1109/istafrica.2014.6880606
|View full text |Cite
|
Sign up to set email alerts
|

Students experiences of using Wiki spaces to support collaborative learning in a blended classroom: A case of Kenyatta and KCA universities in Kenya

Abstract: Abstract:Wiki spaces are simply web pages that allow users to create, edit and share each other's work. This paper shares experiences from a group of students who were using the Wiki spaces in their course work. It attempts to use collaborative knowledge building theory to evaluate the existing Wiki spaces practices in order to inform stakeholders on the power of Wiki spaces in setting students on a knowledge building trajectory. The respondents were 150 university students from Kenyatta and KCA universities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Ochoro (2011) also indicated downsizing negatively associated with organizational support which translated into surviving employees' low level of commitment. Gitonga (2009) revealed that downsizing at Telkom Kenya failed to improve performance, productivity, or profits. Despite downsizing, Telkom has not realized productivity gains and the organization is currently anticipating negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochoro (2011) also indicated downsizing negatively associated with organizational support which translated into surviving employees' low level of commitment. Gitonga (2009) revealed that downsizing at Telkom Kenya failed to improve performance, productivity, or profits. Despite downsizing, Telkom has not realized productivity gains and the organization is currently anticipating negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is the interest of this study to address how best downsizing can be done in order to reduce the negative effects. Gitonga (2009) set out to assess different factors of downsizing and examine their commitment on employee performance, which are the bases for organization performance. The researcher embraced an cross sectional research design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, collaborative learning has been restricted to the classroom environment because of the logistical difficulties in distance learning environment [3]. However, with the introduction of internet technologies in Learning Management Systems (LMSs) such as Wiki Spaces, workshops and forums for collaborative work, new opportunities for student collaboration in an online environment have been created [4]. In Computer Supported Collaborative learning different communication tools both video based and text based can be used to provide a platform for the group members to discuss adequately and express their ideas in the desirable form.…”
Section: Introductionmentioning
confidence: 99%